Analisis Morfosemantik Fi'il Amr dalam Al-Qur'an Surah Al-Kahfi - Saleh, Ummu Sulaimah; Nasrulloh, Nasrulloh (`A Jamiy : Jurnal Bahasa dan Sastra Arab, 2024)
This research is a linguistic research that aims to explain the forms of Fi'il Amr contained in surah Al-Kahf and explain the meaning of fi'il Amr contained in surah Al-Kahf on the review of Morphology or Shorof and Semantics or Ma'ani science. The research design used in this study is descriptive qualitative. Data were collected using data collection techniques in the form of observation and documentation techniques. The data were analyzed using qualitative data analysis techniques, namely analysis through three streams of activities namely reducing data, presenting data, and drawing conclusions. The results showed that (1) There are nine forms of fi'il Amr in surah Al-Kahf found in 21 verses, namely the form اُفْعُلْ, اُفْعُلُوْا, اِفْعِلْ, اِفْعِلُوْا, اِفْعَلُوْا, أَفْعِلْ, أَفْعِلُوْا, فَعِّلْ and فَاعِلُوْا. The most common form of fi'il Amr found in surah Al-Kahf is اُفْعُلْ with 10 data, while the least form of fi'il Amr is اِفْعَلُوْا, أَفْعِلُوْا, فَعِّلْ and فَاعِلُوْا with one data in each form. (2) There are five meanings of fi'il Amr found in surah Al-Kahf, namely: Haqiqi meaning (original meaning), Al-Irsyad (Directing), Ad-Du'a (Request), Ta'jiz (Weakening), and Iltimas (Ordering to the peer). The most meaning of fi'il Amr in surah Al-Kahf is Haqiqi meaning 15 data, while the least meaning is Ta'jiz meaning one data.